2023
DOI: 10.24875/gmm.m18000045
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Candida species from hospitalized patients’ specimens

Abstract: Objective: To identify the most frequent Candida species in specimens from patients hospitalized in different medical centers of Mexico City, with suspected fungal infection. Methods: Specimens were grown on Sabouraud dextrose agar at 28°C for 72 h. In addition, DNA was extracted. Isolates were grown on CHROMagar Candida™, at 37°C for 48 h. The molecular identification was performed by polymerase chain reaction (PCR) using primers specific for four species. Results: Eighty one specimens were processed and incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The incidence of these species agrees with a previous study carried out in Honduras where 167 cultures were evaluated, with C. albicans , C. tropicalis , and C. glabrata being the most commonly isolated species [ 25 ]. Similar results have been reported in Mexico and India [ 27 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of these species agrees with a previous study carried out in Honduras where 167 cultures were evaluated, with C. albicans , C. tropicalis , and C. glabrata being the most commonly isolated species [ 25 ]. Similar results have been reported in Mexico and India [ 27 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Candidiasis is a fungal infection caused by Candida species that features various clinical expressions, including superficial, mucocutaneous, and invasive infection (Camacho-Cardoso et al, 2017). Although Candida species are commensal organisms that presented in healthy individuals and in the natural environment, some of these fungi can become opportunistic pathogens induced by alteration in the host environment, especially in immunocompromised patients (Sadeghi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A second study analyzed 5 different types of clinical samples in Iran, and showed that C. albicans was the predominant species, followed by C. glabrata and C. tropicalis [27]. Another study conducted with eleven types of clinical samples from hospitalized patients with suspected fungal infection in Mexico City showed a higher prevalence of C. albicans, followed by C. tropicalis and C. glabrata [28].…”
Section: Comparison Of Microscan ® Hardychrom ® and Pcr-rflpmentioning
confidence: 99%